2016
DOI: 10.7717/peerj.2669
|View full text |Cite
|
Sign up to set email alerts
|

Low self-concept in poor readers: prevalence, heterogeneity, and risk

Abstract: There is evidence that poor readers are at increased risk for various types of low self-concept—particularly academic self-concept. However, this evidence ignores the heterogeneous nature of poor readers, and hence the likelihood that not all poor readers have low self-concept. The aim of this study was to better understand which types of poor readers have low self-concept. We tested 77 children with poor reading for their age for four types of self-concept, four types of reading, three types of spoken languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 68 publications
1
22
0
2
Order By: Relevance
“…Poor reading is associated with higher risk of school dropout (Daniel 2006), as well as anxiety, depression, low self-concept, and self-harm and suicide (Alexander-Passe 2015;Carroll 2006;Maughan 2003;McArthur 2016).…”
Section: Description Of the Conditionmentioning
confidence: 99%
“…Poor reading is associated with higher risk of school dropout (Daniel 2006), as well as anxiety, depression, low self-concept, and self-harm and suicide (Alexander-Passe 2015;Carroll 2006;Maughan 2003;McArthur 2016).…”
Section: Description Of the Conditionmentioning
confidence: 99%
“…In fact, DD is a complex neurodevelopmental deficit characterized by impaired reading acquisition despite the presence of adequate neurological and sensorial conditions, educational opportunities and normal cognitive level ( 2 ). Different cognitive and behavioral aspects are impaired in DD children such as sleep regulation ( 3 ), postural control ( 4 ), dental occlusion ( 5 ), mood regulation ( 6 ), and self-esteem ( 7 ). In this light, family support may be considered essential, particularly during the transition to adolescence and adulthood ( 8 ), and certainly relevant in pediatric age due to the natural frailty of this crucial period of life.…”
Section: Introductionmentioning
confidence: 99%
“…Towards the end of their first year at school, children's reading performance predicted whether they had either positive or negative academic self-perception with over 70% accuracy. McArthur, Castles, Kohnen, and Banales (2016) reported that poor readers who also had poor foundational oral language skills were at particular risk for lower general self-concept and lower academic self-concept.…”
mentioning
confidence: 99%